(untitled) (Nexo Revista Científica, 2014)
In this work, the influence of the maturation of the clay paste on the technological property plasticity was determined. For this purpose, the treatment of a mixture of powdered clay from three different sites in the region of San Juan de Oriente were used to determine the particle size distribution, plasticity index, soil type and moisture. The clay pastes were prepared with two types of sand (creek and beach) and using the local artisans’ mixture proportions. Then, the pastes rested in dark plastic buckets for 16 days, thus allowing them to mature. One sample was taken every two days; the plasticity index was measured to determine the influence of the maturation on this property. Finally, the sensitivity to drying and the degree of contraction tests of the matured pastes were performed. The initial plasticity index ranges between 17 and 19. After the 16 days, the plasticity index ranges between 22 and 25, thus presenting a tendency to increase linearly as a function of time. However, the pastes prepared with creek sand reached faster a maximum plasticity value of 25. At the same time, it was determined that the pastes suffered a contraction (between 7 and 14 %), with a slight cracking on the surface of the block, but not in the body. DOI: http://dx.doi.org/10.5377/nexo.v27i2.1943